Perbandingan Daya Guna Profilaksis Pethidine 0,5 Mg/KgBB, Tramadol 1 Mg/KgBB dan Ketamin 1 Mg/KgBB untuk Mencegah Shivering Pasca Operasi Laparaskopi dengan Anestesi Umum - Iqbal, Muhammad; Sarosa, Pandit; Sari, Djayanti (Jurnal Komplikasi Anestesi, 2017)
Background: Post anaesthesia shivering is a autonom mechanism compensation against fall body temperature to increased heat body production. Hypothermia during operation is primary cause post anaesthetic shivering. Shivering can increased cardiac activity, intraocular pressure, intracranial pressure and create postoperative discomfort condition. Objective: The aim of this study is compare effectivity of pethidin 0,5 mg/kg, tramadol 1 mg/kg and ketamin 0,5 mg/kg as a prophylactic drug of shivering after laparascopy surgery with general anesthesia. Methods: This study is double blind randomized controlled trial. The subject were 193 patient, male or female with age 18-60, physical status of ASA I and II, who undergo of laparascopy surgery with general anesthesia. Subject were divided into three group. Group P with pethidin 0,5 mg/kg, group T with tramadol 1 mg/kg, group K with ketamin 0,5 mg/kg, drug were diluted with 10 mL normal saline. Prophylactic drugs given when superficial skin closure. Results: Is done measurement systolic blood pressure, diastolic blood pressure, heart rate and body temperature. Measurement done before procedure anaesthesia, during anesthesia and at the recovery room. Conclusion : Shivering assessment began after terminating inhalation anaesthesia agen.